Opus 1. The Artist's Beginnings. - Brams, Koen; Paul, Herman; Wasmer, Marc-Joachim; Jacobs, Steven; van Alphen, Ernst; von Graevenitz, Antje; Lindmayr, Ulrike; Pültau, Dirk (Antwerpen : LLS387, 2015)
Pitz, Hermann ; Tuerlinckx, Joëlle ; Mullican, Matt ; De Keyser, Raoul
artistieke praktijk, eerste werken van een kunstenaar
boek